Frontal EEG asymmetry during symptom provocation predicts subjective responses to intrusions in survivors with and without PTSD. (15th March 2017) - Meyer, Thomas; Quaedflieg, Conny W. E. M.; Weijland, Kim; Schruers, Koen; Merckelbach, Harald; Smeets, Tom
Abstract: Studies suggest that frontal alpha asymmetry is closely linked to psychological adjustment following stressful experiences, such that more left‐sided frontal activation during symptom provocation might predict lower levels of posttraumatic stress disorder (PTSD). Here, we tested whether frontal asymmetry at rest and during exposure to neutral, positive, negative, and trauma‐related images would be associated with PTSD, and particularly with characteristic reexperiencing symptoms. Symptoms were assessed in trauma victims with ( n  = 24) and without PTSD ( n  = 15), using both retrospective measures and 1‐week ambulatory assessments with a diary and a smartphone. While resting frontal asymmetry was unrelated to all retrospective measures, left‐sided activation in response to the negative picture correlated with lower levels of psychopathology. Left‐sided activation in the trauma‐related picture condition was more specifically associated with less emotionally intense intrusions and responses to viewing the picture, even when corrected for other symptoms of psychopathology. These effects tended to increase when participants with possible overreporting tendencies were removed from the analyses. Moreover, trauma victims without PTSD (i.e., relatively more resilient individuals) displayed higher left‐sided frontal activation in response to the negative picture, also when compared with a third group of healthy, trauma‐free individuals ( n  = 15). Our findings suggest that state‐dependent changes in frontal asymmetry could serve as a biological marker of PTSD symptoms and could eventually be used for diagnostic purposes or as a target for neuromodulation interventions. Future studies should establish whether this marker can serve as an early predictor of psychopathology in recently traumatized individuals.